DNA methylation signatures in Blood DNA of Hutchinson–Gilford Progeria syndrome. Issue 2 (19th January 2022) - Bejaoui, Yosra; Razzaq, Aleem; Yousri, Noha A.; Oshima, Junko; Megarbane, Andre; Qannan, Abeer; Potabattula, Ramya; Alam, Tanvir; Martin, George M.; Horn, Henning F.; Haaf, Thomas; Horvath, Steve; et al.
Abstract: Hutchinson–Gilford Progeria Syndrome (HGPS) is an extremely rare genetic disorder caused by mutations in the LMNA gene and characterized by premature and accelerated aging beginning in childhood. In this study, we performed the first genome‐wide methylation analysis on blood DNA of 15 patients with progeroid laminopathies using Infinium Methylation EPIC arrays including 8 patients with classical HGPS. We could observe DNA methylation alterations at 61 CpG sites as well as 32 significant regions following a 5 Kb tiling analysis. Differentially methylated probes were enriched for phosphatidylinositol biosynthetic process, phospholipid biosynthetic process, sarcoplasm, sarcoplasmic reticulum, phosphatase regulator activity, glycerolipid biosynthetic process, glycerophospholipid biosynthetic process, and phosphatidylinositol metabolic process. Differential methylation analysis at the level of promoters and CpG islands revealed no significant methylation changes in blood DNA of progeroid laminopathy patients. Nevertheless, we could observe significant methylation differences in classic HGPS when specifically looking at probes overlapping solo‐WCGW partially methylated domains. Comparing aberrantly methylated sites in progeroid laminopathies, classic Werner syndrome, and Down syndrome revealed a common significantly hypermethylated region in close vicinity to the transcription start site of a long non‐coding RNA located anti‐sense to the Catenin Beta Interacting Protein 1 gene ( CTNNBIP1 ). By characterizing epigenetically altered sites, we identify possible pathways/mechanisms that might have a role in the accelerated aging of progeroid laminopathies. Abstract : Hutchinson–Gilford Progeria Syndrome (HGPS) is characterized by premature and accelerated aging beginning in childhood. DNA methylation age acceleration was not observed in peripheral blood DNA of HGPS patients; however, a significant hypomethylation was detected in CpG sites overlapping solo‐WCGW partially methylated domains.